The Design and Validation of a Self-Report Survey Examining Postsecondary Students’ Perceptions of Success: The Perceived Success in Study Survey (PSISS) (Alberta Journal of Educational Research, 2022)
Postsecondary students' well-being is closely linked to success, which has predominantly been viewed from institutional perspectives rather than student experience. Addressing this gap, students and educators at a New Zealand postsecondary institution identified elements of overall success. Two existing measures were integrated with the student/educator feedback to form a 27-item questionnaire that was piloted twice via social media using snowball recruitment (n=225, n=237). There was strong internal consistency, and factor analysis identified five main factors of influence. The survey is found to be a comprehensive measure of perceptions of success and could be useful in identifying learners' levels of success-promoting attitudes and strategies, which may be of particular relevance during the COVID-19 pandemicKeywords: Motivation; perceptions of success; self-efficacy; student wellbeing; work-life balanceLe bien-être des étudiants de l'enseignement postsecondaire est étroitement lié à la réussite, qui a été principalement considérée du point de vue des établissements plutôt que de l'expérience des étudiants. Pour combler cette lacune, des étudiants et des éducateurs d'un établissement postsecondaire de Nouvelle-Zélande ont identifié les éléments de la réussite globale. Deux mesures existantes ont été intégrées aux commentaires des étudiants et des éducateurs pour former un questionnaire de 27 éléments qui a été testé deux fois via les médias sociaux en utilisant le recrutement en boule de neige (n=225, n=237). La cohérence interne était forte et l'analyse factorielle a permis d'identifier cinq facteurs d'influence principaux. L'enquête s'est avérée être une mesure complète des perceptions de la réussite et pourrait être utile pour identifier les niveaux d'attitudes et de stratégies de promotion de la réussite chez les apprenants, ce qui pourrait être particulièrement pertinent pendant la pandémie de COVID-19. Mots clés : motivation ; perceptions de la réussite ; auto-efficacité ; bienêtre des étudiants ; équilibre entre vie professionnelle et vie privée. This article was accepted under the guest editorship of Dr. Man Wai Chu, University of Calgary, and Pei-Ying Lin, University of Saskatchewan.